Nursery of Penaeus monodon fry in Cage Culture of Intensive Pond at Different Rearing Densities - Budiardi, T.; Salleng, R.D.; Utomo, N.B.P. (Jurnal Akuakultur Indonesia, 2005)
Black tiger shrimp (Penaeus monodon Fab.) culture is now frequently failed as the fault in pond construction and irrigation system, disease break, and younger fry is stocking into pond.  Nursery is a rearing of PL12 to be PL25 at a controlled environmental condition to quickly adapt them on pond condition.   Nursery experiment was conducted in cage culture (1x1x1 m) placed in an intensive pond at density of 250, 500, 750 and 1000 PL/m2, for 14 days rearing.  The results of study indicated that no different in survival and growth of PL was obtained.  Daily growth rate was ranged from 1.10% to 1.53%, while the survival rate was ranged from 86.72-95.60%.  Higher production of shrimp fry (867 PL25) was obtained by rearing PL12 at density of 1000 PL/m2. Keywords: black tiger shrimp, Penaeus monodon, fry, rearing density   ABSTRAK Usaha udang windu (Penaeus monodon Fab.) saat ini banyak mengalami kegagalan akibat konstruksi tambak dan sistem pengairan yang salah, serangan penyakit, dan umur benih yang terlalu muda untuk pemeliharaan ditambak.  Penokolan merupakan pemeliharaan benur pada stadia PL12 menjadi PL25 dalam lingkungan yang relatif terkontrol agar dapat beradaptasi dengan cepat pada lingkungan tambak. Percobaan penokolan dilakukan menggunakan hapa (1x1x1 m) yang dipasang di dalam kolam intensif dengan padat tebar 250, 500, 750 dan 1000 ekor PL/m2, selama 14 hari pemeliharaan. Hasil penelitian menunjukkan bahwa tidak ada perbedaan nyata dalam hal kelangsungan hidup dan pertumbuhannya. Laju pertumbuhan harian udang berkisar antara 1,10% sampai 1,53%, sementara tingkat kelangsungan hidup berkisar 86,72-95,60%.  Produksi benih udang (867 PL25) terbanyak diperoleh dengan memelihara PL12 pada kepadatan 1000 ekor PL/m2. Kata kunci: udang windu, Penaeus monodon, tokolan, kepadatan tebar